2021
DOI: 10.1111/1759-7714.13995
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin bronchoscope combined with virtual bronchoscopic navigation and endobronchial ultrasound for the diagnosis of peripheral pulmonary lesions with or without fluoroscopy: A randomized trial

Abstract: Background Transbronchial lung biopsy (TBLB) is usually performed to obtain a definitive diagnosis for peripheral pulmonary lesions (PPLs). Ultrathin bronchoscopy combined with virtual bronchoscopic navigation (VBN) and radial endobronchial ultrasound (R‐EBUS) are generally considered appropriate diagnostic methods for PPLs; however, they have not yet been explored in combination with fluoroscopy. Therefore, the present prospective randomized controlled trial determined the role of fluoroscopy in ultrathin bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 32 publications
1
33
0
1
Order By: Relevance
“…Following abstract review, 32 articles were selected for full-text review. Of these, 15 articles were excluded according to the protocol, and two studies missed in the database search were added [ 22 , 23 ]. Therefore, 19 studies formed the basis of our systematic review [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following abstract review, 32 articles were selected for full-text review. Of these, 15 articles were excluded according to the protocol, and two studies missed in the database search were added [ 22 , 23 ]. Therefore, 19 studies formed the basis of our systematic review [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our study was not registered prior to the review, but we followed the suggested PRIS-MA protocol. Asano 2013 [30] Oki 2015 [31] Diez-Ferrer 2019 [35] Oki 2019 [13] Sumi 2020 [37] Sumi 2021 [39] Zheng 2021 [23] Total (95% Cl) Heterogeneity: τ 2 = 0.0272; χ 2 = 20.09, df = 7 (p < 0.01); I 2 = 65% Test for overall effect: Z = -2. 29 Oki 2009 [28] Oki 2015 [31] Oki 2019 [13] Sumi 2020 [37] Sumi 2021 [39] Zheng 2021 [23] Total (95% Cl)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns estudos mostraram que o desempenho diagnóstico da CBTB nas LPP é igualmente bom com ou sem fluoroscopia. (19,20) Portanto, é razoável supor que é possível realizar a criobiópsia sem o auxílio da fluoroscopia. Neste estudo, demonstramos a utilidade da CBTB guiada por EBUS radial com bainha guia sem fluoroscopia na avaliação de LPP.…”
Section: Discussionunclassified
“…Therefore, it is reasonable to recommend the bronchoscopic sample collection of these nodules under VBN-rEBUS guidance, which is feasible and safe. 16 , 17 For another part of nodules with the S/D ratio less than 1.84 may not be visualized by rEBUS, which may have a poor diagnostic yield by bronchoscopic biopsy. Even with the assistance of fluoroscopy, the diagnostic yield of those nodules may still be limited.…”
Section: Discussionmentioning
confidence: 99%